Comparison of brake reaction time in younger and older drivers - Ashok, J.; Suganthi, V.; Vijayalakshmi, I. (International Journal of Research in Medical Sciences, 2016)
Background: Reaction time (RT) is the time taken for an individual to respond to a stimulus. Brake reaction time is the time taken for the driver to visualize an object and to press the brake pedal. BRT should be assessed in drivers for analysing their speed of mental processing and physical response. Objective of the study is to assess the BRT in male drivers and compare BRT between younger and older drivers. Methods: Male drivers between age groups of 18-65 years were included. Study is conducted in a stationary car. An in-house built; vehicle braking reaction timer is fixed to the electric circuit of the braking system in the car. The device is connected with laptop. The subject is instructed to press the brake pedal when the light changed. Results: The correlation between BRT and age was found to be negative in less than 55 years age group, the R value is found to be -0.094. Above the age group of 55 years there was a positive correlation, the R value was found to be +0.458. Conclusions: The decrease in BRT in <55 years age group could be due to the experience/training, which has increased the driving skills and speed of processing.